2. EVALUATION OF THE PSOFA SCORE AND PRISM SCORE IN THE PREDICTION OF MORTALITY IN SEVERELY ILLATE PATIENTS ADMISSITED TO THE EMERGENCY DEPARTMENT (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the application of the pSOFA score and the PRISM score; to compare the value of the pSOFA score and the PRISM score in predicting mortality in critically ill patients.Subjects and methods: All patients admitted to the Emergency Department – Nghe An Obstetrics and Pediatrics Hospital with severe or life-threatening illness from March 2024 to September 2024. The pSOFA and PRISM scores were evaluated by the area under the ROC curve (AUROC).Results: The pSOFA and PRISM scores in the group of deceased patients were 13,65 ± 2,519 and 15,45 ± 5,443, respectively, significantly higher than in the group of surviving patients. The AUROC of the pSOFA in predicting mortality was ,975 (95% CI: 0,954 – 0,995) with a sensitivity of  99% and a specificity of 89,4%. The AUROC of PRISM was 96,3% (95% CI: 0,932 – 0,993) with a sensitivity of  95% and a specificity of 87,4%.Conclusions: Mortality was proportional to the pSOFA and PRISM scores; the pSOFA and PRISM scores were both able to separate the surviving and non-surviving groups well, and the pSOFA score had a higher value in predicting mortatily in critically ill children.
Keywords: pSOFA; PRISM; mortality prediction